Clays and Clay Minerals, Vol. 57, No. 4, 444–451, 2009. - Hrachova, Jana; Komadel, Peter; Chodak, Ivan (My University, 2009)
Enhancement of the physico-chemical properties of elastomers can be achieved by the addition of fillers, such as silica, but the search for less expensive alternative materials continues. The objective of this study was to investigate natural or organically modified clay minerals as such an alternative. Organoclays modified by quaternary ammonium cations with three methyl groups and longest alkyl chains of different lengths were prepared by ion-exchange reaction of the commercial product JP A030 (Envigeo, Slovakia) based on Jelsˇovy´ Potok bentonite with organic salts: tetramethylammonium (TMA) chloride, octyltrimethylammonium (OTMA) bromide, and octadecyltrimethylammonium (ODTMA) bromide. Physico-chemical characterizations of the organo-clays used as fillers in rubber nanocomposites and their mechanical properties were measured using Fourier transform infrared (IR) spectroscopy, which provided information on the chemical composition of the mineral and on the amount of organic moieties adsorbed. X-ray diffraction analysis (XRD) was used to monitor the arrangement of organic chains in galleries of montmorillonite and showed that the longest-chain alkylammonium ODTMA+ ions were intercalated between layers, adopting a pseudotrimolecular conformation, while OTMA+ and TMA+ were in monomolecular arrangement. Surface areas were measured by sorption of N2 and ethylene glycol monoethyl ether. Natural rubber-clay nanocomposites were prepared by melt intercalation, in some cases also with addition of silica, a conventional reinforcing filler. The microstructure of montmorillonite in these composites was characterized by XRD analysis. The effect of clay and organo-clays loading from 1 to 10 phr (parts by weight per hundred parts of rubber) on stress at break, strain at break, and Modulus 100 (M100) was investigated by tensile tests. Filler ODTMA-JP A030 appears to be the most effective among the organoclays; surprisingly similar values of composite elongation and strength were obtained with unmodified bentonite JP A030.
Natural Rubber Nanocomposites With Organo-modified Bentonite
gsccm57405-hra.pdf-- 356KB
Keywords: Periodicals; Geology; Clay; Layered Silicate; Mechanical Properties; Nanocomposite; Organo-clay; Polymer